Application of The Game Simon Says for Elementary English learning - Nurmalia Dwi Pangesti; Zumiatul Farida; Fatika Aurellia Anissa Balqis (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to find out how English learning can run well with a more effectivelearningmodelin accordancewith 2013 curriculum learning.Previous learning onlyrefers to teachers who make learning seem boring and students are not interestedin learning, for that teachers are required to make ways to make learning easier.learning is not monotonous and applies the 2013 curriculum with more modern,effective, efficient, and fun learning. Students have different skills and their owncharacteristics which of course affect learning in the classroom. In this study, it isknown that the selection of English learning methods using games can make iteasier for students to understand the material presented by the teacher. Thislearning strategy with games is suitable for encouraging students compared tousing the lecture method in general which seems boring and makes students lessunderstanding of the material. Learning with games, teachers must provide clearand concise instructions using demonstrations for students to understand theinstructions. Games can help students create a fun atmosphere, relax lessons,motivate and improve students' writing skills. The selection of games here usesSimon Says which can train students to communicate and be more active inlearning English inclass.